Approaching the Power Logarithmic and Difference Means by Iterative Algorithms Involving the Power Binomial Mean - Mustapha Raïssouli (International Journal of Mathematics and Mathematical Sciences)
Introducing the notion of cross means we give iterative algorithms involving the power binomial mean and converging to the power logarithmic and difference means. At the end, we address a list of open problems derived from our present work.